Differential equations for dummies - Holzner, Steven. 4 0 16; 5 (Hoboken, New Jersey : Wiley Publishing Inc., 2008)
A comprehensive guide to differential equations that covers first, second, and higher order equations, advanced techniques, and other related topics; and includes worked problems.
Includes index.
Adult.
Keywords: 2 -- 0; 6; Differential equations. -- 20; 20; 2